Religion and religious fundamentalism in Nigeria: Boko Haram's claims to truth - Medinat A. Malefakis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
The aim of this research is to analyze the local plausibility of religious claims to truth in Boko Haram's ideology. As global jihadi organizations continue to operate under-ground in the face of successful counter-terrorist actions against them, religious underpins seem to be one of the few cohesive glues holding them afloat and keeping the flow of blind support unending. Is this however enough for unwavering loyalty to a terrorist group declared 'technically defeated' by the state? The research analyses why Boko Haram's ideology of radical Islam resonated with many (mostly young) people in Nigeria's northeast. It does so by looking, on the one hand, at the narratives the insurgency creates with reference to globally circulating ideologies based on interpretations of the Quran and the Hadiths, and, on the other, by analyzing the socio-economic and cultural situation of the local and Islamic communities in northern Nigeria that seem to make the group's claims potent.
Keywords: 300